Outcome of phacoemulsification and extracapsular cataract extraction: A study in a district hospital in Malaysia - Sagili Chandrasekhara, Reddy; Thanigasalam Thanigasalam, Thevi; Chandrasekharan, Shantakumar (2014)
Aim: The aim of the study was to compare the outcomes of phacoemulsification (Phaco) and extracapsular cataract extraction (ECCE) in a district hospital setting. Methods: A retrospective analysis was done from the medical records of the patients who underwent Phaco and ECCE in Temerloh District Hospital, Pahang state between October 2009 and September 2010. The age, gender and ethnicity of the patients, intraoperative and postoperative complications, and the best corrected visual acuity at the last follow-up visit were noted. Statistical analysis was done using Stata Software Version 11.0. The results of the two procedures were compared. Results: Out of the 179 cataract surgeries performed, 146 cases were Phaco and 33 were ECCE. In our study, 82 were men and 97 were women. The age of patients ranged from 39 to 82 years; majority of the patients (71.3%) were more than 60 years of age. There was a significant association between type of surgery and outcome of visual acuity (p = 0.001). There was no significant association between intraoperative complication and type of surgery (p = 0.166). Postoperative complications of the surgeries were not significantly different. Good visual outcome was noted in 80.1% of eyes operated by Phaco compared to 48.5% of eyes operated by ECCE procedure. Conclusion: Since the visual outcome was significantly better in Phaco compared to ECCE procedure (p = 0.001), we recommend that Phaco equipments should be supplied in the district hospitals with adequate facilities for performing intraocular surgery